Breeding and Lactation Efficiencies, Production Profile, Productive Herd Life and Lifetime Productivity of Gir Cows in their Home Tract - Gadariya, MR; Vataliya, PH; Murthy, KS; Ghajbi, PU (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Breeding and lactation efficiencies (BE and LE), parity-wise production profile, productive herd life and lifetime milk production (LTMP) of Gir cows (N=309), based on 1363 calvings during 1991 to 2010 at Cattle Breeding Farm, JAU, Junagadh were studied. Age at first calving (AFC) and calving interval (CI) of Gir cows were 1527.76±14.17 and 481.22±4.86 days, respectively. CI ranged from 386 to 505 days among different lactations. When AFC and CI were taken into account together, BE of the cows as per Tomar (BE-T) was estimated to be 86.91±0.49 %. About 17 % of Gir cows in the herd calved for the first time at <42 months of age (Av. 37.04 month) and 38 % of the cows had less than 14 months of CI. Lactation period (LP) of Gir cows varied significantly (P<0.05) from 230 days to 335 days showing an increasing trend with increase in no. of parity. Overall LP of Gir cows was 281.02±4.56 days, LE being 61.07±1.10%. Total lactation milk yield (TLMY) and standard lactation milk yield (SLMY) of Gir cows averaged 2006.29±48.77 and 1819.73±45.44 lit, respectively. Milk yield increased significantly (P<0.05), with increase in no. of parity, reaching peak TLMY (2425 lit) and SLMY (2303 lit) in 5th lactation. TLMY was 2134 to 2362 lit, and SLMY 1950 to 2110 lit in 6th to 8th lactation. Productive herd life averaged 3107.87±81.40 days (8.51 years). Mean number of calvings during lifetime was 4.25±0.15. A total of 19- 25 % of the total cows performed in the herd for more than 12 years, (average being 14.6 years) and for > 6 lactations. Gir cows produced 9988.71±649.08 lit LTMP. LTMP of Gir cows was significantly associated with both, the BE and LE (r =0.23 to 0.25). MSLMY showed significant (P<0.05) correlation (r=0.31 to 0.37) with BE-W and LE. Association of AFC was significant with BE-T (r=0.26). The 1st and 2nd CI showed a correlation (r= 0.57 to 0.59, P<0.01) of high magnitude with BE-W. The findings revealed that Gir cows in the herd are worth- retaining in the herd till 8th lactation with satisfactory breeding efficiency of about 87 % for economically viable sustainable dairy farming.